PENGARUH GAMBAR DAN TULISAN PERINGATAN KESEHATAN MEROKOK TERHADAP PERILAKU PEROKOK REMAJA DI PEKANBARU - Muhammad Januari; Suyanto, " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Smoking health warning pictures and writings can provide stimuli to smokers resulting in behavioral changes. The theory used in this research is the theory of S-O-R (Stimulus-Organism-Response). The purpose of this study was to determine the effect of smoking health warning images on adolescent smoker behavior, the influence of smoking health warnings on adolescent smoking behavior and the influence of smoking health warning pictures and writings on adolescent smoker behavior in Pekanbaru.This research uses quantitative research methods, with data collection techniques, namely through questionnaires. The sample in this study amounted to 166 respondents using the Accidental Sampling method. The chosen respondents were teenagers who were in the age range of 15-19 years who were domiciled in Pekanbaru. The data analysis method used is simple linear regression analysis and multiple linear regression. Data processing is carried out with the SPSS version 23 program.The results obtained from a simple linear regression analysis in this study are that there are effects of smoking health warning images on adolescent smoker behavior of 22.7% which are included in the level of low influence. The simple linear regression results also showed that there was an influence on smoking health warnings on adolescent smokers' behavior by 37.5% which was included in the level of low influence. And the results of multiple linear regression indicate that smoking health warnings and writings together influence the behavior of adolescent smokers in Pekanbaru. Processed results of 39.6% are included in the category of low level of influence.Keywords: Cigarette Pictures, Smoker Behavior